Fairness spillovers: The case of taxation - Thomas Cornelissen; Oliver Himmler; Tobias König (Center for Economic Studies and ifo Institute (CESifo), 2010)
It is standardly assumed that individuals adjust to perceived unfairness or norm violations in precisely the same area or relationship where the original offense has occurred. However, grievances over being exposed to injustice may have even broader consequences and also spill over to other contexts, causing non-compliant behaviour there. We present evidence that such 'fairness spillovers' can incur large economic costs: A belief that there is unfairness in taxation in the sense that the rich don't pay enough taxes is associated with a twenty percent higher level of paid absenteeism from work.
Keywords: H31; H26; D63; 330; fairness; beliefs; taxation; work morale; Steuergerechtigkeit; Wahrnehmung; Soziale Werte; Spillover-Effekt; Arbeitsethik; Soziale Kosten; Schätzung; USA